Uniform Design Method for punching shear in flat slabs and column bases. (1st April 2017) - Kueres, Dominik; Siburg, Carsten; Herbrand, Martin; Classen, Martin; Hegger, Josef
Highlights: Evaluation of punching shear design provisions according to Eurocode 2. New Uniform Design Method for punching shear in flat slabs and column bases. New databank consisting of 476 punching tests on flat slabs and column bases. Abstract: The punching shear design of flat slabs and column bases was revised with the introduction of Eurocode 2. While in many former codes the punching shear resistance was determined regardless of the type of member, in Eurocode 2 two different design equations for flat slabs and column bases were introduced. Additionally, different control sections for flat slabs and column bases were defined. The differentiation between flat slabs and column bases and especially the iterative design procedure for the determination of the punching shear resistance of column bases require great effort in daily practice. Based on the punching shear provisions according to Eurocode 2, a new Uniform Design Method (UDM) for flat slabs and column bases is developed. The derivation of the design method is described in detail. To verify the changes in the current design provisions, the new design method is evaluated using large databanks for flat slabs and column bases without and with shear reinforcement as well as systematic test series.